UGMRT search for cold gas at z ∼ 1–1.4 towards red quasars. Issue 1 (4th November 2019) - Dutta, R; Raghunathan, S; Gupta, N; Joshi, R
ABSTRACT: We present results from our search for H i 21-cm and OH 18-cm absorption at z ∼ 1–1.4 towards red quasars showing strong Mg ii absorption using upgraded Giant Metrewave Radio Telescope. The quasars J1501 + 1822 and J1521 + 5508 show multiple strong associated Mg ii absorption at z ∼ 1.1 and signature of reddening in their optical spectra. We report the detection of H i 21-cm absorption towards J1521 + 5508 at the systemic redshift of the quasar, with $N(\rm{H\, {\small I}}$ ) = (1.2 ± 0.2) × 10 20  cm −2 for spin temperature of 100 K and unit covering factor. The H i 21-cm absorption is offset from the blueshifted strong Mg ii absorbers by ≳1500 km s −1 . We do not detect H i 21-cm absorption at the redshift of the associated Mg ii absorption and at the systemic redshift towards J1501 + 1822. We argue that lack of one-to-one correspondence between Mg ii and H i 21-cm absorption could be related with clumpiness of the neutral gas and the radio and optical sightlines probing different volume of the gas. We find that the presence of strong associated Mg ii absorption and reddening in the optical spectra of the quasars lead to an increased detection rate of associated H i 21-cm absorption at z ≥1. We also report non-detection of intervening OH absorption ([OH]/[H i ] ≤ (1–4)× 10 −8 ) at z  = 1.3 towards two red quasars, J0850 + 5159 and J0852 + 3435, which show strong metal and H i 21-cm absorption and the 2175 Å dust extinction bump.